Tindak Tutur Ekspresi Kecaman Bahasa Banjar - Rissari Yayuk (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2016)
This research studies the speech acts of expressive criticism on Banjar language. It aims to describe the realization of (1) the speech acts of expressive criticism forms on Banjar language, and (2) the maxims violation on expressive criticism acts on Banjar language. The method of this research is descriptive qualitative. Data of this research was elicited through recording technique, note-taking and bibliography reviewing, from June 2015 to December 2015. This research concludes that that (1) the speech acts of expressive criticism forms on Banjar language were related to jobs, parts of the body, things wearing, and kinship, and (2) the maxims violation on expressive criticism acts on Banjar language are violations of acceptances, compatibility, mercy, and wise.